An improved distribution network reconfiguration method based on minimum spanning tree algorithm and heuristic rules. (November 2016) - Li, Hongwei; Mao, Wenjin; Zhang, Anan; Li, Chao
Highlights: New reconfiguration method combines MST Algorithm and improved heuristic rules. The algorithm does not rely on the initial distribution network topology. The amount of candidate switches needed to be evaluated is greatly reduced. The new algorithm can generally get the optimal solution with higher efficiency. Abstract: This paper presents an improved distribution network reconfiguration method with the goal to minimize active power loss. The proposed method combines the minimum spanning tree (MST) algorithm and improved heuristic rules. It consists of three procedures. The first procedure calculates the branch (edge) weights with bus (vertex) voltages, and then carries out preliminary optimization with MST algorithm to get a local optimal solution. The second procedure gets alternative optimal solution based on the improved heuristic rules. Then during the third procedure, the optimal solution can generally be obtained through correcting the results. The algorithm does not rely on the initial network topology. The local optimal solution, solved by MST algorithm, provides a favorable initial condition for the subsequent optimization procedures. Further with the improved heuristic rules, the amount of the candidate switches can be significantly reduced. Two typical test systems, 33-bus system and 69-bus system, and a real 210-bus MV utility distribution system verified the feasibility and effectiveness of the proposed method. The method has higher efficiency and can be used to the large distribution systems.